Highly efficient triphenyl(3-sulfopropyl)phosphonium functionalized phosphotungstic acid on silica as a solid acid catalyst for selective mono-allylation of acetals - Kamble, Sumit B.; Shinde, Suhas H.; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2015)
Silica supported phosphotungstic acid functionalized with triphenyl(3-sulfopropyl)phosphonium (PW-Si/TPSP) was developed as a solid acid catalyst for C-C bond formation via Hosomi-Sakurai allylation of acetals. Functionalization of PW as well as its binding to silica was confirmed by solid state P-31-NMR and Si-29-NMR, respectively. Among the various catalysts prepared, the 30% PW loaded (30PW-Si/TPSP) catalyst gave an excellent yield of homoallyl ethers (HAEs) via selective mono-allylation of acetals with allyltrimethylsilane. A plausible reaction pathway has also been proposed in which the strong Bronsted acid sites of 30PW-Si/TPSP play an important role in activating the acetals to form the corresponding oxonium cations. The versatility of our catalyst was demonstrated for the allylation of a wide variety of acetals while its stability was established in five successful recycling runs.

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Integrated production of diesel fuel precursors from carbohydrates and 2-methylfuran over Sn-mont catalyst - Shinde, Suhas H.; Rode, Chandrashekhar V. (ChemistrySelect, 2018)
A TfOH-catalyzed highly efficient synthesis of biologically active (E)-2-cyanoacrylamides and 3-substituted azetidine-2,4-diones has been reported with 64-94% yields under metal-free conditions. The reaction proceeds through sequential Knoevenagel condensation/stereoselective in situ monohydration of nitrile or C-N cyclization protocol in one-pot. The attractive features of this tandem process are moderate reaction conditions, high atom economy, broad substrate scope, gram-scale reaction and ease of operation.

Lignocellulose-derived platform molecules: an introduction - Shinde, Suhas H.; Hengne, Amol; Rode, Chandrashekhar V. (Recent Advances in Development of Platform Chemicals, 2020)
Fossil feedstocks such as crude oil, natural gas, and coal are formed by natural anaerobic decomposition of buried organisms for a period of more than 650 million years. On the other hand, agrobiomass is quick to grow and becomes a renewable source of chemical and fuel production through processing in a biorefinery.
Keywords: Biomass; Biorefinery Cellulose; Lignocellulose Petrofinery; Platform molecules